The transformative capacity of evaluation: A perspective from the Evaluator - Ghiano, Celeste (Revista Aval, 2020)
This article aims to make some links between hermeneutical paradigms of social science research and the pluralistic perspectives of Public Policies’ Evaluation. Special emphasis is placed on the importance of evaluator's Reflexivity, as a constructor of meanings based on the performativity of evaluation structures; and as a transformer of realities. Likewise, a reflection is developed about the importance of inquiring in new ways of teaching and learning to evaluate, linked to our local and regional realities. We will then make a special zoom about a South Epistemology / ies, which include the empowerment of the public affected by a policy, program or project to be evaluated, based on participatory and democratic approaches and with cultural sensitivity.